The Elements of Moral Philosophy - Rachels, James, 1941-2003 (Boston McGraw-Hill College, 1999)
This text offers a clear introduction of the major philosophical theories of morality, explaining why each theory has been accepted by some thinkers but rejected by others. To illustrate the theories, and to reveal their implications, subjects such as abortion, euthanasia, and famine are discussed.
include Index
Keywords: Ethics